AVALIAÇÃO DAS PROPRIEDADES TÉRMICAS DE TIJOLOS DE TERRA CRUA (ADOBES) - Dal Soglio, Carolina Rodrigues; Meller, Bruna Just; Olinger, Marcelo Salles; Marinoski, Deivis Luis; Güths, Saulo; Mizgier, Martin Gabriel Ordenes (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The objective of the present study is to characterize the thermal properties of 4 samples of unfired earth bricks (adobes). The properties were verified through laboratory tests and deductive calculations. The thermal conductivity of the samples varied according to the soil and the relative humidity in the environment. The range of measured thermal conductivity (k) varied between 0.46 and 0.67 W/m.K. The minimum wall thickness was calculated to attend the required Thermal Capacity (CT) and Thermal Transmittance (U) of the Brazilian standards for walls in all bioclimatic zones.